Ocimum kilimandscharicum 4CL11 negatively regulates adventitious root development via accumulation of flavonoid glycosides - Lavhale, Santosh G.; Kondhare, Kirtikumar R.; Sinthadurai, Veenothini S.; Barvkar, Vitthal T.; Kale, Rutuja S.; Joshi, Rakesh S.; Giri, Ashok P. (Plant Journal, 2024)
4-Coumarate-CoA Ligase (4CL) is an important enzyme in the phenylpropanoid biosynthesis pathway. Multiple 4CLs are identified in Ocimum species; however, their in planta functions remain enigmatic. In this study, we independently overexpressed three Ok4CL isoforms from Ocimum kilimandscharicum (Ok4CL7, -11, and -15) in Nicotiana benthamiana. Interestingly, Ok4CL11 overexpression (OE) caused a rootless or reduced root growth phenotype, whereas overexpression of Ok4CL15 produced normal adventitious root (AR) growth. Ok4CL11 overexpression in N. benthamiana resulted in upregulation of genes involved in flavonoid biosynthesis and associated glycosyltransferases accompanied by accumulation of specific flavonoid-glycosides (kaempferol-3-rhamnoside, kaempferol-3,7-O-bis-alpha-l-rhamnoside [K3,7R], and quercetin-3-O-rutinoside) that possibly reduced auxin levels in plants, and such effects were not seen for Ok4CL7 and -15. Docking analysis suggested that auxin transporters (PINs/LAXs) have higher binding affinity to these specific flavonoid-glycosides, and thus could disrupt auxin transport/signaling, which cumulatively resulted in a rootless phenotype. Reduced auxin levels, increased K3,7R in the middle and basal stem sections, and grafting experiments (intra and inter-species) indicated a disruption of auxin transport by K3,7R and its negative effect on AR development. Supplementation of flavonoids and the specific glycosides accumulated by Ok4CL11-OE to the wild-type N. benthamiana explants delayed the AR emergence and also inhibited AR growth. While overexpression of all three Ok4CLs increased lignin accumulation, flavonoids, and their specific glycosides were accumulated only in Ok4CL11-OE lines. In summary, our study reveals unique indirect function of Ok4CL11 to increase specific flavonoids and their glycosides, which are negative regulators of root growth, likely involved in inhibition of auxin transport and signaling.
Keywords: 4-Coumarate-CoA ligase; 7-O-bis-alpha-l-rhamnoside; adventitious root; auxin transport; Flavonoids; kaempferol-3; Ocimum kilimandscharicum; quercetin-3-O-rutinoside; rootless